2013
DOI: 10.4070/kcj.2013.43.8.519
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Clinical Outcomes among Patients with Metabolic Syndrome and Acute Myocardial Infarction

Abstract: Background and ObjectivesMetabolic syndrome (MetS) is an important risk factor for cardiovascular disease. However, the clinical outcome of acute myocardial infarction (AMI) with MetS has not been well examined. The purpose of this study was to evaluate the clinical outcomes of AMI patients with MetS.Subjects and MethodsWe evaluated a total of 6352 AMI patients who had successful percutaneous coronary interventions and could be identified for MetS between 2005 and 2008 at 51 hospitals participating in the Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…Studied patients were those implanted with first-generation DES (sirolimus-or paclitaxeleluting stent) or bare-metal stent in the studies by Xu D. et al, whereas our study investigated those treated with second-generation DES (EES or R-ZES). In addition, several studies including our previous study showed that MetS was a poor predictor of clinical outcome after coronary intervention in high risk patients, but not in the overall AMI population [26,27]. Thus, discrepancy in the results between our study and the previous studies might be attributed to the study population.…”
Section: Comparison Of the Patient-related Outcome In Patients Implancontrasting
confidence: 79%
See 2 more Smart Citations
“…Studied patients were those implanted with first-generation DES (sirolimus-or paclitaxeleluting stent) or bare-metal stent in the studies by Xu D. et al, whereas our study investigated those treated with second-generation DES (EES or R-ZES). In addition, several studies including our previous study showed that MetS was a poor predictor of clinical outcome after coronary intervention in high risk patients, but not in the overall AMI population [26,27]. Thus, discrepancy in the results between our study and the previous studies might be attributed to the study population.…”
Section: Comparison Of the Patient-related Outcome In Patients Implancontrasting
confidence: 79%
“…Moreover, Xu D. et al reported that MetS was a poor prognostic factor in patients treated with stent and even in patients treated with DES in a recent meta-analysis [8]. In addition, several studies including our previous study showed that MetS was a poor predictor of clinical outcome after coronary intervention in high risk patients [26,27].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To confound matters further, controversy exists about the assumption that MetS is useful in predicting mortality beyond its components 13, 14, 15. The prognostic importance of MetS compared with that of its individual components has repeatedly been challenged.…”
mentioning
confidence: 99%
“…The prognostic importance of MetS compared with that of its individual components has repeatedly been challenged. Several studies argued that not all individual components of MetS contributed to the increased risk of all‐cause mortality 13, 14, 15. This risk was significantly predicted by impaired fasting glucose (IFG) in all subjects, as well as by IFG and low high‐density lipoprotein (HDL) cholesterol in women among an Italian population 18, 19, 20…”
mentioning
confidence: 99%